Polyostotic Fibrous Dysplasia in McCune-Albright Syndrome Demonstrated on 68Ga-DOTATATE PET/CT. (December 2016) - Hennessy, Grace; Shetty, Deepa; Loh, Han; Bui, Chuong; Le, Ken; Mansberg, Robert
Abstract : Abstract: A 33-year-old woman with McCune-Albright syndrome was referred for a 68 Ga-DOTATATE PET/CT study for evaluation and staging of a biopsy-proven pancreatic tail neuroendocrine tumor. The scan demonstrated intense focal octreopeptide uptake corresponding to the known neuroendocrine tumor at the pancreatic tail/splenic hilum. There was no evidence of octreopeptide-avid metastases. Diffuse octreopeptide uptake was demonstrated in multiple bones involving the right side of the skeleton. The concurrent CT demonstrated corresponding expansile lucent changes consistent with the known fibrous dysplasia.